Portafolio de marcas: un marco conceptual - Chailan, Claude (2003)
In the last twenty years, the knowledge of the brand has been considerably enriched, in tandem with the importance it has acquired. But it is necessary to deepen in one aspect of this topic: the relationship between the brands of the same company from the perspective of the organization of their respective territories. This dimension has been very little studied, although it is part of the day-to-day of the managers, who wonder about the most relevant brand strategies to achieve success. The methodological works emphasize the need to operationalize the concepts to allow their measurement. The relationship between unobservable concepts (for example, performance and brand portfolio) is estimated through the study of the empirical relationship in three certain dimensions of these concepts. Thus, finding the measurable dimensions of a concept allows us to account for it and measure some of its components. This article proposes to operationalize the concept of brand portfolio and highlight its measurable dimensions.